Fifty years of European ungulate dietary studies: a synthesis. Issue 11 (27th July 2020) - Spitzer, Robert; Felton, Annika; Landman, Marietjie; Singh, Navinder J.; Widemo, Fredrik; Cromsigt, Joris P. G. M.
Abstract : Over recent decades, ungulate populations across Europe have undergone a rapid recovery. While this constitutes a conservation success, there is increasing concern about their impacts on shared resources with humans. Understanding ungulate food choices is crucial for predicting such impacts. Numerous studies have focused on single species or communities at narrow spatial scales. Here, we used 265 published diets from 87 European studies to investigate patterns of resource use by four common deer species (moose Alces alces, red deer Cervus elaphus, roe deer Capreolus capreolus and fallow deer Dama dama ), and wild boar Sus scrofa at the continental scale. On average, deer diets separated mostly along a gradient from grass to browse. Fallow deer diets contained the most and moose diets the least amount of grass, but we also found large intraspecific variation among all deer species. Diets of roe deer, a presumed browser, frequently contained ≥ 25% grass. Wild boar diet contained grass in amounts similar to red deer but otherwise differed strongly from deer diets. All five ungulate species shifted to eating higher proportions of woody browse during winter. Habitat influenced variation in intraspecific diets, but the proportions of key forage types related to feeding type (i.e. grass for intermediate feeders red and fallow deer, and shrubs for the browsers moose and roe deer) remained fairly consisted across habitat types. In northern and central Europe, diet similarity between roe deer and red deer was highest during winter and spring and lowest during summer and autumn but remained constant across the seasons in southern Europe. We foresee that, as interspecific interactions driven by land‐use and climatic changes increase across Europe, further monitoring and testing will be needed to understand the dynamics of dietary niche partitioning among ungulates.